Hematological malignancies are associated with a lower interferon-a blocking activity than solid tumors. - Karmaniolas, K; Dalamaga, M; Liatis, S; Kaskara, A; Rigopoulos, A; Migdalis, I N (Res Commun Mol Pathol Pharmacol, 2005)
UNLABELLED: Interferon (IFN) and especially IFN-alpha exhibit clinical anti-tumor activity against various types of malignant diseases. Natural inhibitors to various cytokines and IFNs have been documented in vitro as well as in vivo. IFN inhibitors have been implicated for the ineffectiveness of IFN treatment in malignant neoplasias. The aim of this study was to investigate the incidence of the IFN inhibiting activity in serum from patients with haematological malignancies versus patients with solid tumours, as an effort to explain, just in part, the different response of these patients to IFN treatment. PATIENTS AND METHODS: Ninety patients with a clinically evident solid tumour and forty-six patients with haematological malignancies were included in the study. Serum samples from all patients were collected before any treatment and stored at -70 degrees until use. Controls sera were selected from 50 apparently healthy blood donors. Interferon-inhibiting activity as well as endogenous IFN-like activity were determined in all serum samples in a cell line highly sensitive to IFN. RESULTS: There was no endogenous IFN-like activity in any of the patients' group or controls' group. Sera from patients with haematological malignancies exhibited IFN-blocking activity at a lower percentage (21.7%) in comparison to sera from patients with solid tumours (56.6%, P<0.001), but at a significantly higher percentage in comparison to sera from controls (P<0.01). CONCLUSIONS: The fact that IFN inhibitors were detected at a significantly lower percentage in sera from patients with haematological malignancies versus patients with solid tumours, could explain in part the better response of the haematological malignancies to IFN treatment.
Keywords: Aged; Aged, 80 and over; Antineoplastic Agents; Cell Line, Tumor; Cytopathogenic Effect, Viral; Female; Hematologic Neoplasms; Humans; Interferon Type I; Interferon-alpha; Male; Middle Aged; Neoplasms; Recombinant Proteins